2021
DOI: 10.1128/spectrum.00394-21
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota Protects Bees from Invasion by a Bacterial Pathogen

Abstract: Bacteria living within guts of animals can provide protection against infection by pathogens. Some pathogens have been shown to use a molecular weapon known as a T6SS to kill beneficial bacteria during invasion of the mouse gut.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 60 publications
2
58
0
Order By: Relevance
“…Furthermore, the communities established by native strains resemble natural bee gut communities in composition and in their activation of bee genes related to immunity and development ( figure 3 ). These results are consistent with preliminary trials showing that the administration of natural isolates can restore microbiota disrupted by antibiotics and can defend against infection by opportunistic bacterial pathogens [ 31 , 70 ]. Although promising, establishment does not imply efficacy in promoting host health, and the benefits of native bee gut strains remain untested at the hive level.…”
Section: Future Prospects For Honeybee Probioticssupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the communities established by native strains resemble natural bee gut communities in composition and in their activation of bee genes related to immunity and development ( figure 3 ). These results are consistent with preliminary trials showing that the administration of natural isolates can restore microbiota disrupted by antibiotics and can defend against infection by opportunistic bacterial pathogens [ 31 , 70 ]. Although promising, establishment does not imply efficacy in promoting host health, and the benefits of native bee gut strains remain untested at the hive level.…”
Section: Future Prospects For Honeybee Probioticssupporting
confidence: 91%
“…Potentially, probiotic treatment with natural gut strains from the native microbiota could replenish perturbed gut communities. Recent experimental studies have shown that bees mono-colonized with single or multiple strains of native gut bacteria can control the overproliferation of S. marcescens in the bee gut [ 11 , 70 ]. Similar overproliferation is observed in microbiota-deprived bees or antibiotic-treated bees [ 70 ].…”
Section: Approaches and Challenges For Probiotic Treatmentsmentioning
confidence: 99%
“…It has been shown that honeybees with a conventional microbiome structure have higher survival following challenges with the opportunistic pathogen bacteria ( 11 ). This protection may be due to the physical block of the colonization through killing or suppressing pathogens ( 28 ) or through priming the host immune system by the gut symbionts ( 29 ). Therefore, we first determined if core bee gut members inhibit the invasion of H. alvei in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to playing important roles in digestion and harvesting energy ( 37 , 38 ), commensal bacteria are important factors determining pathogen infection. Intestinal microbiota can confer protection against intestinal pathogens in three potential ways: (i) through indirect activation of the host immune response ( 39 ); (ii) through direct microbe-microbe competition for nutrients ( 39 , 40 ); or (iii) through antagonism between microbes (e.g., via Type VI secretion system) ( 28 , 41 ). In a first step toward exploring the molecular mechanism underlying the observed protection, we found that strains from Gilliamella and Lactobacillus did not inhibit the growth of H. alvei on the plates (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This species has been reported as a symbiont in some insect groups (Manzano‐Marín & Latorre, 2014), yet it can act as a pathogen in other groups such as bees (Raymann et al, 2018). Its principal functions provide protection against parasites while improving host fitness (Muhammad et al, 2017; Steele et al, 2021).…”
Section: Resultsmentioning
confidence: 99%